Blizzard! : the storm that changed America - Murphy, Jim, 1947- (New York : Scholastic, 2000)
Presents a history, based on personal accounts and newspaper articles, of the massive snow storm that hit the Northeast in 1888, focusing on the events in New York City.
Includes bibliographical references (p. 125-132) and index.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Junior High School.
5.9.
5.9
Keywords: Blizzards -- New York (State) -- New York -- History -- 19th century -- Juvenile literature; Blizzards -- New York (State) -- New York; Blizzards; New York (N.Y.) -- History -- 1865-1898 -- Juvenile literature; New York (N.Y.) -- History -- 1865-1898.; New York (N.Y.) -- History